High-quality, large-scale, semi-thin, & ultra-thin sections of the optic nerve in large animals: An optimized procedure. (June 2022) - Li, Mengyun; Lu, Shenjian; Huang, PingPing; Xia, Tian; Yu, Zhonghao; Jiang, Wenhao; Mao, Yiyang; Yang, Chen; Yu, Shuaishuai; Wu, Wencan; Zhang, Yikui
Abstract: Large animal model of optic nerve (ON) injury is an essential tool for translational medicine. Perfusion fixation with paraformaldehyde is mainly used for preparing the semi-thin (1–2 μm thick) and ultra-thin (<0.5 μm thick) sections of the ON tissues. However, this conventional fixation technique in large animals needs a large volume of fixatives, which increases the risk of toxic exposure and is environmentally unfriendly. Additionally, fixed residual ON cannot be used for other tests that require fresh tissue samples. Although conventional immersion fixation is feasible for preparing a semi-thin section of the ON in small animals (0.2–0.6 mm in diameter), it faces technical challenges when fixing the ON of large animals (3 mm in diameters), as increased diameter limits the permeability of the fixatives into deeper tissue. Therefore, we optimized the immersion-fixation method to obtain high-quality, large-scale, semi-thin, and ultra-thin sections for the ON of goat and rhesus macaques. Using this optimized technique, the ON microstructure was well preserved throughout the entire area of 1.5*1.5 square millimeters, allowing confident quantification of axon density/diameter on semi-thin section and identification of specific organelles and glial cells on ultra-thin sections. Furthermore, the optimized technique is a quick, simple, and environmentally friendly fixation method. Notably, the ON regions of large animals with or without an intact neurovascular system can be prepared for light and electron microscopy. In contrast, the residual unfixed ON from the same animal can be further utilized for experiments such as tissue culture and biomolecular tests. Highlights: The optimized procedure with immersion fixation circumvents the drawbacks of perfusion fixation in large animals. Large scale, high-quality semi-thin sections of the optic nerve in goat and rhesus macaque were obtained. Identification of organelles and glial cells can be made on the ultra-thin sections of the optic nerve from large animals.